Application of CIPP flipped lining method in the rehabilitation of old gas pipelines - You Yun; Wang xinxin; Wang Zhongyi; Wang Yuyan; Chen Hao (Scientific Reports)
Abstract With the increase of urban gas pipeline operation time, more and more underground gas pipelines are facing various problems, and old gas pipelines urgently need to be updated and repaired. Realizing the comprehensive excavation, demolition, and replacement of old pipes with new ones poses pain points such as high construction difficulty, repair costs, and uncertainty of routing construction planning. Therefore, the implementation of trenchless repair and transformation of old gas pipelines has positive and practical significance. The CIPP flipped lining repair technology, as an emerging trenchless pipeline repair technology, provides an efficient and cost-effective solution for the repair of old gas pipelines. A case study on the application of CIPP flipped lining method was conducted for the rehabilitation project of Liangshen Road gas pipeline in Weituo Industrial Park, Chongqing. By comparing the characteristics of different trenchless pipeline repair techniques, the technical adaptability of CIPP flipped lining method was analyzed, and the construction parameter design, key process flow, and construction difficulties of using CIPP flipped lining to repair gas pipelines were explored and revealed, as well as the control of engineering quality impact. Practice has shown that CIPP flipped lining can provide a feasible technical choice for the preventive repair of urban gas pipelines. The repaired pipeline performance meets the operational requirements of urban gas pipelines, and has broad prospects and promotion value. It can provide reference for the non-excavation repair and utilization of old gas pipelines in the future.